(untitled) (Research, Society and Development, 2021)
An odontogenic infection can originate from a dental element or its supporting structures. Periodontal diseases, endodontics, defective restorative treatments and caries are associated with its most common causes. When identified in its early stage, treatment may include endodontic intervention, replacement of restorative material, periodontal treatment and localized drainage. The objective of this paper is to report a clinical case of a patient who presented a case of odontogenic infection at an advanced stage, discussing the correct diagnosis, its surgical treatment and pharmacological protocol. Male patient, black, 31 years old,with a history of toothache and submandibular abscess with a 22-day evolution time. When performing contrast-enhanced computed tomography of the face and neck, a collection, suggestive of purulent, was observed in submandibular and supraclavicular fascial spaces. The recommended protocol consisted of exploratory cervicotomy of deep fascial spaces together with drainage, removal of material for culture and broad-spectrum antibiotic therapy. The severities of odontogenic infections that affect deep cervical spaces are known, bringing with them the risk of mediastinitis and airway complications. Therefore, safe handling and the surgeon’s mastery of early diagnosis and quick and safe intervention delimit complications and increase the chances of cure.